ART PEDAGOGIKA ZAMONAVIY TA’LIM-TARBIYANING INTEGRATIV OMILI - Haydarov, X.H. (SCIENCE and SOCIETY, 2025)
This article describes the meaning and content of the art pedagogical approach in the educational process.
Keywords: Art pedagogy; content-essence; purpose; objectives; art therapy; art therapeutic pedagogy; aesthetic pedagogy; correctional; cathartic; regulatory